Avaliação do perfil de citocinas plasmaticas e da dosagem da carga proviral na mielopatia associada ao HTLVI: estudo comparativo entre portadores assintomáticos e pacientes com HAM/TSP - Ana Lucia Borges Starling (2010)
The occurrence of HTLV-1 associated myelopathy / tropical spastic paraparesis (HAM/TSP) seems to be related to the patients immunologic profile with an increase of proinflammatory cytokines INF-y, TNF- and IL-2. These alterations are well established in individuals with HAM/TSP. In such patients, proviral load has been considered as a potential marker of disease activity. Conversely, asymptomatic individuals with HTLV-1 show an increase of IL- 10, an anti-inflammatory cytokine considered as a potential immune regulator. The objective of the present study was to compare the plasma cytokine profile and the proviral load of individuals with HAM/TSP. The participants were selected from the open cohort of referred blood donors infected with HTLV-1 and patients with HAM/TSP followed up by the Interdisciplinary Group of Research on HTLV-1 (GIPH). The participants were divided into four groups: 21(19, 4%) blood donors (controls), 27(25, 0%) HTLV-1-asymptomatic carriers; 32(29,6%) with few HAM/TSP symptoms (potential HAM/TSP); and 28(25, 9%) with HAM/TSP. The cytokine tested for al participants were: IL-4, IL-10, IL-2, IL-6, TNF- and IFN- y. The proviral load was tested in the individuals with HTLV-1. The groups were compared in order to identify which cytokines were associated with HAM/TSP and which ones were correlated with the high proviral load. In the comparative analysis, it was observed in the HAM/TSP group a significant increase of cytokines INF-y (p=0.030, OR=7.6, IC=0.57- 101.79), IL-6 (p=0.002) and IL-4 (p=0.034, OR=0.83 IC=0.07 -10.55), as well as a tendency to the increase of TNF- (p=0.058, OR=2.8, IC=0.06-8.82). The proviral load correlated with HAM/TSP (p<0,001). These patients presented higher values of INF-y and a tendency to lower values of IL-2 and TNF- .. The present study confirmed the correlation between higher proviral load and greater inflammatory response for HAM/TSP patients, which corroboratesthe hypothesis that the neurological lesions associated with HAM/TSP are due to the host immunological response against the virus. This response would not be modulated as occurs in the TLV-1-asymptomatic carrier